PENGARUH PENGETAHUAN PRODUK DAN KEPERCAYAAN TERHADAP MINAT MASYARAKAT MENGGUNAKAN ULANG APLIKASI OVO (STUDI PADA MASYARAKAT KECAMATAN KISARAN BARAT) - MARDELIA DESFRIDA; BENHUR PAKPAHAN; MUHAMMAD ZUARDI; CAHYOGINARTI CAHYOGINARTI; SUDARSONO SUDARSONO (LP2MTBM MAKARIOZ, 2023)
This study aims to determine the effect of product knowledge and trust on public interest in reusing the OVO application. This research is an associative study and the type of data used is quantitative data. The data used are primary and secondary data. The data analysis method used is descriptive analysis and multiple linear regression. The population in this study were the people of Kisaran Barat District, whose number was unknown and the sample of this study was 96 people. The results of this study indicate that the effect of product knowledge and trust simultaneously has a significant effect on public interest in reusing the OVO application. Partially, the influence of product knowledge has a positive and significant effect on public interest in reusing the OVO application, trust has a positive and significant effect on public interest in reusing the OVO application.